Cultural Influences in Central Asia and Contiguous Territories at the Turn of the First and Second Millennia C.E. (Based on the Materials of Small-Form Toreutics). Issue 1 (3rd April 2019) - Korol, Galina G.
Abstract : Examined in the article are medieval small-form toreutics [decorated nonferrous metal objects] from the territory of Mongolia, the south of the Russian Far East, and Tibet. Tibetan amulets (including medieval ones) have decoration comparable to that of belt adornments from the Kyrgyz Khaganate from the ninth through tenth centuries (Saian-Altai), the period of its dominance in Central Asia. On the basis of a critical and historical comparative analysis of the material, several levels of possible cultural influence in Central Asia and on contiguous territories have been identified.